The effects of pulsatile cardiopulmonary bypass on acute kidney injury - AK, KORAY; ARSAN, SİNAN (SAGE PUBLICATIONS LTD, 2012)
Purpose: Protective effect of pulsatile flow cardiopulmonary bypass (CPB) on the occurrence of acute renal injury is still a matter of debate. The objective of this study was to compare the effects of pulsatile and non-pulsatile cardiopulmonary bypass on kidneys using Urinary neutrophil gelatinase-associated lipocalin (NGAL) and interleukin-18 (IL-18) as the markers of renal injury. Methods: 85 consecutive patients with normal preoperative renal function were prospectively enrolled in the study. Pulsatile perfusion (Group P) and non-pulsatile perfusion (Group NP) was used in 42 and 43 of the patients, respectively, during aortic cross-clamping period. NGAL and IL-18 were analyzed using ELISA in urine samples obtained preoperatively, and at 2, 12, and 24 h after CPB. Results: There was no significant difference between the groups in terms of perioperative renal function tests. IL-18 levels measured at 12 h after CPB were significantly lower in Group p, compared to Group NP (p<0.05). Urinary NGAL levels measured at 2 and 12 h were higher in Group NP; however, the difference was insignificant. In the subgroup of patients with a cross clamp time >= 45 minutes (pulsatile CPB, group P1, n = 33; non-pulsatile CPB, group NP1, n = 33), IL-18 levels measured at 12 hours after CPB were significantly lower in Group P1. Urinary NGAL concentrations measured at 2 and 12 hours in Group P1 were also significantly lower than that in Group NP1 (p = 0.048 and 0.043, respectively). Conclusions: Low IL-18 and NGAL levels found in the pulsatile perfusion group might suggest the use of pulsatile flow resulted in better kidney protection.
Keywords: Neutrophil gelatinase-associated lipocalin; NGAL; Interleukin-18; IL-18; Cardiopulmonary Bypass; Cardiac surgery; GELATINASE-ASSOCIATED LIPOCALIN; PEDIATRIC HEART-SURGERY; NEONATAL PIGLET MODEL; VITAL ORGAN RECOVERY; ACUTE RENAL INJURY; CARDIAC-SURGERY; NONPULSATILE PERFUSION; INTRAAORTIC BALLOON; BLOOD-FLOW; DYSFUNCTION